Body resistance on and under the water surface - Jiskoot, J.; Clarys, J. P. (Swimming Technique, 1988)
Average to good males (N = 43) were towed in a 200-m tank on the surface and at a depth of 60 cm at speeds ranging from 0.7 to 2.0 m per second. Both tests were repeated some months apart with the first test being conducted in a water temperature of 18 and the second at 24 degrees celsius. The resistances increased in both conditions upon the retesting. This could be due to the water temperature change. Resistance increased in the vicinity of 20+% when towing velocity was increased from 1.5 to 1.9 m/s. That amount is far in excess of previously published values of 11%. Resistance was found to be greater when totally submerged than when swimming on the surface. Under water resistances are due to total frictional resistance plus total eddy resistance while on the surface there is wave resistance, and partial frictional and eddy resistance. Implication: It is preferable to perform on the surface rather than under the water because of the resistances incurred in swimming.